Effect of structure–ground interaction on shrinkage stresses in foundation reinforced concrete elements - Grosel Jacek; Pakos Wojciech (Studia Geotechnica et Mechanica, 2025)
This paper presents a numerical analysis of the shrinkage of reinforced concrete foundations on the ground, known as mat foundations. It presents Finite Element Method (FEM) calculations of a beam and its verification with analytical solutions. Two numerical models of mat foundations have been adopted for the purpose of this study. The first model is a foundation resting directly on the ground, that is, on an elastic Winkler base. The second numerical model consists of layers, that is, a mat foundation and a substructure (lean concrete), taking into account the frictional forces between these layers. The Mohr–Coulomb model was used in the analyses. Conclusions were drawn from the numerical analyses on the influence of the soil substrate on the magnitude of the shrinkage stresses. Modelling the interaction between the foundation and a concrete sole using elastic bonds is clearly suboptimal. Using friction to model this connection is a better approach as it avoids underestimating shrinkage stresses. The differences can be up to an order of magnitude.